Overexpression of LINC00673 Promotes the Proliferation of Cervical Cancer Cells - Huang, Sheng-Kai; Ni, Ruo-Xuan; Wang, Wen-Jie; Wang, Di; Zhao, Mei; Lei, Cheng-Zhi; Sun, Xiao-Jie; Huang, Chang-Zhi; Bai, Ping; Che, Yi-Qun; Xu, Jian-Ping (Frontiers in Oncology, 2021)
Objective To study the expression of LINC00673 in cervical cancer and cervical intraepithelial neoplasia (CIN) and to explore the role of LINC00673 in the development of cervical cancer. Methods The expression of LINC00673 in serum from cervical cancer patients, CIN patients, and healthy participants was detected by RT-qPCR. The function of LINC00673 in cervical cancer cells was analyzed using in vitro and in vivo experiments. Results Our results revealed that serum LINC00673 levels were highest in cervical cancer patients, followed by patients with CIN and healthy controls. In vitro experiments demonstrated that overexpression of LINC00673 enhanced the proliferation and cell cycle progression of HeLa and SiHa cells. In vivo experiments showed that the tumor weight and volume of nude mice subcutaneously injected with LINC00673-overexpressing HeLa cells were larger than those of nude mice injected with control cells (P < 0.05). Western blotting showed that cell cycle-related proteins cyclin A2 and cyclin E and interstitial-associated proteins Snail and N-cadherin were upregulated and p53 signaling pathway-related proteins were downregulated in LINC00673-overexpressing HeLa and SiHa cells. Conclusion LINC00673 plays an important role in the development of cervical cancer and may serve as a new therapeutic target for cervical cancer.